Health-related quality of life, functional impairment and comorbidity in people with mild-to-moderate chronic kidney disease: a cross-sectional study. Issue 8 (6th August 2020) - Fraser, Simon DS; Barker, Jenny; Roderick, Paul J; Yuen, Ho Ming; Shardlow, Adam; Morris, James E; McIntyre, Natasha J; Fluck, Richard J; McIntyre, Chris W; Taal, Maarten W
Abstract : Objectives: To determine the associations between comorbidities, health-related quality of life (HRQoL) and functional impairment in people with mild-to-moderate chronic kidney disease (CKD) in primary care. Design: Cross-sectional analysis at 5-year follow-up in a prospective cohort study. Setting: Thirty-two general practitioner surgeries in England. Participants: 1008 participants with CKD stage 3 (of 1741 people recruited at baseline in the Renal Risk in Derby study) who survived to 5 years and had complete follow-up data for HRQoL and functional status (FS). Primary and secondary outcome measures: HRQoL assessed using the 5-level EQ-5D version (EQ-5D-5L, with domains of mobility, self-care, usual activities, pain/discomfort and anxiety/depression and index value using utility scores calculated from the English general population), and FS using the Karnofsky Performance Status scale (functional impairment defined as Karnofksy score ≤70). Comorbidity was defined by self-reported or doctor-diagnosed condition, disease-specific medication or blood result. Results: Mean age was 75.8 years. The numbers reporting some problems in EQ-5D-5L domains were: 582 (57.7%) for mobility, 166 (16.5%) for self-care, 466 (46.2%) for usual activities, 712 (70.6%) for pain/discomfort and 319 (31.6%) for anxiety/depression. Only 191 (18.9%) reported no problems in any domain. HRQoL index values showed greater variation among those with lower FS (eg, for those with Karnofsky score of 60, the median (IQR) EQ-5D index value was 0.45 (0.24 to 0.68) compared with 0.94 (0.86 to 1) for those with Karnofsky score of 90). Overall, 234 (23.2%) had functional impairment. In multivariable logistic regression models, functional impairment was independently associated with experiencing problems for all EQ-5D-5L domains (mobility: OR 16.87 (95% CI 8.70 to 32.79, p<0.001, self-care: OR 13.08 (95% CI 8.46 to 20.22), p<0.001, usual activities: OR 8.27 (95% CI 5.43 to 12.58), p<0.001, pain/discomfort: OR 2.94 (95% CI 1.86 to 4.67), p<0.001, anxiety/depression: 3.08 (95% CI 2.23 to 4.27), p<0.001). Higher comorbidity count and obesity were independently associated with problems in mobility, self-care, usual activities and pain/discomfort: for three or more comorbidities versus none: (mobility: OR 2.10 (95% CI 1.08 to 4.10, p for trend 0.002), self-care: OR 2.64 (95% CI 0.72 to 9.67, p for trend 0.05), usual activities: OR 4.20 (95% CI 2.02 to 8.74, p for trend <0.001), pain/discomfort: OR 3.06 (95% CI 1.63 to 5.73, p for trend <0.001)), and for obese (body mass index (BMI) ≥30 kg/m 2 ) versus BMI <25 kg/m 2 : (mobility: OR 2.44 (95% CI 1.61 to 3.69, p for trend <0.001), self-care: OR 1.98 (95% CI 1.06 to 3.71, p for trend 0.003), usual activities: OR 1.82 (95% CI 1.19 to 2.76, p for trend 0.019), pain/discomfort: OR 2.37 (95% CI 1.58 to 3.55, p for trend <0.001)). Female sex, lower FS and lower educational attainment were independently associated with anxiety/depression (ORs 1.60 (95% CI 1.18 to 2.16, p 0.002), 3.08 (95% CI 2.23 to 4.27, p<0.001) and 1.67 (95% CI 1.10 to 2.52, p 0.009), respectively). Older age, higher comorbidity count, albuminuria (≥30 mg/mmol vs <3 mg/mmol), lower educational attainment (no formal qualifications vs degree level) and obesity were independently associated with functional impairment (ORs 1.07 (95% CI 1.04 to 1.09, p<0.001), 2.18 (95% CI 0.80 to 5.96, p for trend <0.001), 1.74 (95% CI 0.82 to 3.68, p for trend 0.005), 2.08 (95% CI 1.26 to 3.41, p for trend <0.001) and 4.23 (95% CI 2.48 to 7.20), respectively). Conclusions: The majority of persons with mild-to-moderate CKD reported reductions in at least one HRQoL domain, which were independently associated with comorbidities, obesity and functional impairment. Trial registration number: National Institute for Health Research Clinical Research Portfolio Study Number 6632.